Is It Attachment Style or Socio-Demography: Singlehood in a Representative Sample - Petrowski, Katja; Schurig, Susan; Schmutzer, Gabriele; Brähler, Elmar; Stöbel-Richter, Yve (Frontiers in Psychology, 2015)
Since the percentage of single adults is steadily increasing, the reasons for this development have become a matter of growing interest. Hereby, an individual’s attachment style has come under close scrutiny in the context of its possible association to the partnership status. In the current study, a comparison of an individual’s attachment style, gender, age, education, and income was carried out in regard to the partnership status. Furthermore, an analysis of variance was computed to compare the attachment style within different groups. A sample of 1,676 representative participants between 18 and 60 years was investigated (M = 41.0, SD = 12.3); 54% were female, and 40% were single. Attachment-related attitudes were assessed employing the German version of the Adult Attachment Scale (AAS). Single adult males did not show a more anxious attachment style than single adult females, or females in relationships. Paired individuals between 18 and 30 years showed greater attachment anxiety than single individuals, while single individuals between 31 to 45 years showed greater attachment anxiety than paired individuals. In addition, single individuals more frequently had completed high school in contrast to paired individuals. Concerning the attachment style, the individuals who had not completed high school showed less faith in others. Concerning age, single individuals between 46 and 60 years, felt less comfortable with closeness and showed less trust in others than paired individuals. Logistic regression showed that individuals who felt comfortable depending on others, were older on average, showed more attachment anxiety, and had less formal education did not remain single. An income below €2000/month was linked to a nearly 13-fold increase in the likelihood of being single. In sum, the attachment style had a differential age-dependent association to remaining single versus being in a relationship. Education also played a role, especially in respect to trusting others.